THE CONSTRUCTION OF ETHIC CONDUCT AT STUDENT´S FORMATION OF PHYSICAL EDUCATION: PERSPECTIVE OF TEACHER´S ACTION (Fiep Bulletin - online, 2017)
Ethics and vocational training are now subjects that are in evidence. In this sense it is necessary to consider thecomplementary relation between them in the process of training and teaching practice, therefore, the teacher's role requires decisionsand actions that have implications éticas.Este study aims to analyze the contributions of teachers in higher education for constructionof ethical conduct in the training of physical education students and specifically identify the foundations of ethics and its implicationsfor the training of physical education students; analyze the teachers' actions as a reference for the ethical conduct of futureprofessionals and discuss the contribution of teachers outlook for the construction of ethics of physical education students. Theresearch is qualitative type of descriptive and exploratory nature, the instrument was a questionnaire of questions, closed and open inits maioria.Como inclusion criterion was selected three professors who acted more in the formation of the first class Bachelor ofPhysical Education in the state of Maranhao, giving three or more subjects from first to seventh period, being a female and two males.It is concluded that the design of professional ethics in higher education are linked to the actions taken, with justice and questions ofvalues. And the teachers' actions that influence the construction of the conduct of the students are a real relationship between teacherand student, exchange of knowledge, compliance schedules, lack of releases and actions to reflect the issues of a society.